2005
DOI: 10.1038/modpathol.3800237
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphomas with clonal immunoglobulin V3–21 gene rearrangements exhibit fewer genomic imbalances than mantle cell lymphomas utilizing other immunoglobulin V genes

Abstract: A preferential use of one particular immunoglobulin variable heavy chain gene, V H 3-21, has recently been reported in mantle cell lymphoma, where almost all of these V H 3-21 þ mantle cell lymphomas showed usage of the same light chain V k gene (V k 3-19) and also had a tendency towards improved prognosis. These findings suggested that V H 3-21 þ mantle cell lymphomas constitute a distinct subgroup, possibly with antigen stimulation involved in disease pathogenesis. In this study, we applied the comparative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 19 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Most studies have found no relationship between the mutational status of the clonogenic IGHV genes and the evolution of the disease (23,27). Although a tendency to longer survival has been reported for patients with a high number of somatic mutations or carrying specific IGHV genes (18,21,22,28). Moreover, a subset of patients with a very indolent clinical course and SOX11 negative expression seem to express IGs with a high load of somatic hypermutation (SHM) (20).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have found no relationship between the mutational status of the clonogenic IGHV genes and the evolution of the disease (23,27). Although a tendency to longer survival has been reported for patients with a high number of somatic mutations or carrying specific IGHV genes (18,21,22,28). Moreover, a subset of patients with a very indolent clinical course and SOX11 negative expression seem to express IGs with a high load of somatic hypermutation (SHM) (20).…”
Section: Introductionmentioning
confidence: 99%